PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE PADA MATERI BANGUN DATAR - Gofita Destiviani Pratama; Tri Joko Raharjo; Eko Handoyo; Bambang Subali; Nuni Widiarti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Based on the problems found in pre-research at SD Negeri Gondoriyo Semarang City, the lack of use of interactive learning media in mathematics lessons on flat building material makes students uninterested in learning, resulting in low student math learning outcomes. This study aims to determine the feasibility of interactive learning media based on Articulate Storyline in math lessons for grade 2 students. This type of research is development research or research and development (R&D). The instrument used to collect data consists of a validation sheet by experts and a student response questionnaire on a small scale test consisting of 10 students to determine the readability and applicability of Articulate Storyline-based interactive media. Based on the results of media expert validation obtained 87%, material expert validation obtained 93% and linguist validation obtained 94% with a very feasible category. Then based on the results of a small-scale test of interactive media based on Articulate Storyline, the teacher's response obtained 90% with a very feasible category and the students' response obtained 94%. Articulate Storyline media proved to be very feasible to be developed in grade 2 math learning.